Non-linear Impacts of Product Market Competition on Earnings Quality - Mohammad Hossein Ghaemi (Shahid Bahonar University of Kerman, 2017)
Increasing earnings quality raises costs and benefits together. Also, product market competition affects economic variables with multiple impacts. These resulted in conflicts over findings from the researches regarding regression analysis for the relationship between earnings quality and competition in product markets. In these researches, inconsistent results showed that actual relationship between the two variables is of nonlinear form. In this paper, the nonlinear relationship between earnings quality and product market competition has been studied. To measure competition in the product market, total business environment and homogeneity of the production in the market were considered in general, and earnings qualities along with market competition were measured by three and for criteria, respectively. Also, in addition to firm-year values, industry-year values were used to test the proposed hypotheses in different states. The data from 91 companies listed in the Tehran Stock Exchange in the years 2008-2013 were used. The findings from nonlinear regression analysis showed an inverted U-shaped relationship between earnings quality and competition. But, this was not held for potential competition. These findings were also remained unchanged when the study turns from firm-year values to industry-year values.